2018
DOI: 10.1002/jocb.229
|View full text |Cite
|
Sign up to set email alerts
|

Off‐Task Social Breaks and Group Creativity

Abstract: This study investigates the effect of off-task breaks, where individuals engage in a collective offtask activity, on group creativity. Using an experimental method comprising 36 groups of 5 individuals, the relationships between different types of off-task group break and performance in creative tasks post-break are explored. When compared to the no-break case, it is seen that offtask breaks, in which all individuals participate in the group activity, lead to more original ideas being generated post-break. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…But time and different levels of activity are essential for creativity, in particular to allow for an incubation period. So interspersing the creative process with short breaks, alone or together, seems to be a successful strategy for creativity (Bernstein et al., 2019; Breslin, 2019). Such changes in pace of work should be considered in further research combining individual and group creativity.…”
Section: Discussionmentioning
confidence: 99%
“…But time and different levels of activity are essential for creativity, in particular to allow for an incubation period. So interspersing the creative process with short breaks, alone or together, seems to be a successful strategy for creativity (Bernstein et al., 2019; Breslin, 2019). Such changes in pace of work should be considered in further research combining individual and group creativity.…”
Section: Discussionmentioning
confidence: 99%
“…Breaks can optimize idea generation when the break is a structured off-topic team activity. Additionally, Breslin (2019) found that idea feasibility did not improve from the pre- to post-break period regardless of break condition. The process of idea evaluation is often used to refine ideas for feasibility and appropriateness (Mumford et al, 2002).…”
Section: Meeting Influencesmentioning
confidence: 93%
“…In contrast, research on the influence of breaks on team creativity is a bit more understood. Breslin (2019) conducted an experiment that examined team creative output before and after various break conditions. Members either took an off-topic break where no member interaction occurred (i.e., sitting in silence), an off-topic break where members worked to a common goal without structure provided (i.e., building a model tower), and an off-topic break where members worked to a common goal with comparatively more structure provided (i.e., a sorting task with necessary information distributed among members), or took no break.…”
Section: Meeting Influencesmentioning
confidence: 99%
“…Intuiting can also be a collective activity through the TLO 26,6 interactions of the entrepreneurial team and wider network. Recent research in psychology points to important cognitive, social and motivational factors that enhance the creative process through social interactions (Paulus and Brown, 2007;Breslin, 2018). In this way, the process of association through which ideas emerge occurs through interpersonal interactions, as ideas are triggered through the contributions of other members (Paulus, 2000).…”
Section: Intuitingmentioning
confidence: 99%
“…Routines here are not cumbersome, institutionalized rules, but repeated habitual behaviors completed within the entrepreneurial team. The incorporation and management of such routine tasks within the daily lives of the entrepreneurial team (Breslin, 2018), can have profound implications for the process of intuiting. Loasby (2007) conjectured about the link between routines and entrepreneurial behaviors, arguing that the creation of routines freed up valuable cognitive processing resources needed for other more pressing entrepreneurial activities, such as the processing of idea sets noted above.…”
Section: Routinizingmentioning
confidence: 99%